APPLICABILITY OF kDNA-PCR FOR ROUTINE DIAGNOSIS OF AMERICAN TEGUMENTARY LEISHMANIASIS IN A TERTIARY REFERENCE HOSPITAL - Marcela M. Satow; Edite H. Yamashiro-Kanashiro; Mussya C. Rocha; Luiza K. Oyafuso; Rita C. Soler; Paulo C. Cotrim; Jose Angelo L. Lindoso (Revista do Instituto de Medicina Tropical de São Paulo, 2013)
SUMMARY This study evaluated the applicability of kDNA-PCR as a prospective routine diagnosis method for American tegumentary leishmaniasis (ATL) in patients from the Instituto de Infectologia Emílio Ribas (IIER), a reference center for infectious diseases in São Paulo - SP, Brazil. The kDNA-PCR method detected Leishmania DNA in 87.5% (112/128) of the clinically suspected ATL patients, while the traditional methods demonstrated the following percentages of positivity: 62.8% (49/78) for the Montenegro skin test, 61.8% (47/76) for direct investigation, and 19.3% (22/114) for in vitro culture. The molecular method was able to confirm the disease in samples considered negative or inconclusive by traditional laboratory methods, contributing to the final clinical diagnosis and therapy of ATL in this hospital. Thus, we strongly recommend the inclusion of kDNA-PCR amplification as an alternative diagnostic method for ATL, suggesting a new algorithm routine to be followed to help the diagnosis and treatment of ATL in IIER.